FACTORS THAT INFLUENCE COMMITMENT TO EMPLOYEE DUTIES AT RESEARCH CENTER FOR MARINE AND FISHERIES PRODUCT PROCESSING AND BIOTECHNOLOGY - Syahrian Syahrian (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
The background of this research was to look up how far the problem of the educational background of employees, level of income in the form of salaries and benefits, career paths for employee in the organization / institution can affect employee commitment to the task. The objectives of this research was to determine the effect of commitment to the task with the problem of the educational background of employees, to determine the effect of commitment to the task with the problem of the level income in the form of salaries and allowances of the employees, to determine the effect of commitment to the task with the problem of career employees at the research center for marine and fisheries product processing and biotechnology. The design of this research applies using data collected from the calculation and collection of questionnaires. Data analysis used in this research was the collected data conducted a preliminary analysis using statistics is to describe the data for each variable. The result of this research conclude that have the positive effect of the educational background of employees, level of income in the form of salaries and allowances of officers and career employees at the organization / institution with a commitment to the task at the research center for marine and fisheries product processing and biotechnology. Keywords: Factors that influence, commitment, employee duties.